ACTR-22. INITIAL TREATMENT OF GBM WITH A KETOGENIC DIET ALONG WITH RADIATION AND CHEMOTHERAPY: CLINICAL OUTCOMES. (11th November 2019) - Schwartz, Kenneth; Noel, Mary; Nikolae, Michele; Olson, Karl; Zakem, Micheal; Elnabtity, Mohamed; Clark, Justin; Figueroa, Bryan; Chang, Howard
Abstract: INTRODUCTION: Combining an adjuvant ketogenic diet (KD) with standard therapy of radiation and chemotherapy right after tissue diagnosis is feasible and safe. We report outcomes of a pilot clinical trial study using a KD combined with radiation and chemotherapy as initial therapy for glioblastoma (GBM). METHODS: Eligibility criteria included: 1. Tissue diagnosis; 2. Age over 18; 3. ECOG performance status of 2 or better; and 4. Not having diabetes or being pregnant. An isocaloric KD diet with 3:1 weight ratio of fat to combined weight of carbohydrate and protein was supervised by an experienced dietitian and maintained with initial radiation and chemotherapy for 6 weeks. RESULTS: 9 patients (8M, 1F, mean age 45) completed the prescribed 6 week trial. Blood counts, chemistries, lipid profiles and uric acids were not markedly changed. Ketosis was maintained for the 6 week study period with blood ketone and glucose levels checked twice daily. 3 younger patients (mean age 28 at diagnosis) are working and show no progression of their gliomas at 49 (IDH +), 31 (IDH WT with methylated MGMT), and 32 (IDH WT) months since diagnosis. 6 older male patients (mean age 54) have died at 25, 25, 13, 12, 9 and 9 months after diagnosis. A recent report of 6 additional older male pts mean age 53 tx with a KD with daily checks of blood ketones showed limited survival ranging from 12–19 mo. (van der Louw accepted for pub in "Therapeutic Advances in Medical Oncology"). CONCLUSION: KD may be a helpful in initial treatment of GBM patients, especially in younger patients. Additional studies are needed. However, since 12 older male patients have not substantially benefited from the KD, we suggest that future evaluations of the efficacy of KD for GBM be focused towards younger patients.